International migration and citizenship today - Steiner, Niklaus (Abingdon, Oxon ; New York, NY : Routledge, 2023)
"This completely revised and updated textbook explores the moral, economic, political, and cultural dimensions of the movement of people across international borders. In style and substance, this book is designed to spark thoughtful discussions and to challenge students to draw their own conclusions to questions such as: How should democracies balance the rights of immigrants with those of citizens? What exactly constitutes persecution and how should we define a refugee? How should democracies allocate citizenship? Can and should a distinction between voluntary and forced migration be made, and does one group of migrants deserve admission more than the other? What does a reasonable border policy look like? The rise of populism, the vote for Brexit, and the unprecedented flow of refugees around the world are all evidence that these questions remain highly salient, controversial, and unresolved. Intended as the main text for undergraduate classes on international migration the book will also appeal to broad survey courses on world politics, comparative politics, international relations, world history and more specialized courses on human rights and nationalism"--
The nature of this book -- Admitting authorized immigrants -- Excluding unauthorized immigrants -- Impact of immigrants -- Guest workers -- Modern efforts to protect refugees -- Asylum in liberal democracies -- Citizenship, nationalism and national identity -- Citizenship, membership and belonging -- Beyond conventional approaches.
OCLC-licensed vendor bibliographic record.
Keywords: Emigration and immigration -- History -- 21st century; Emigration and immigration -- Government policy; Immigrants -- Social conditions -- 21st century; Immigrants -- Economic conditions -- 21st century; Citizenship -- History -- 21st century; POLITICAL SCIENCE / General; POLITICAL SCIENCE / International Relations / General